UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN KEMANGI (Ocimum basilicum L.) TERHADAP BAKTERI Streptococcus mutans - Syarifuddin, Aminah Nur; Purba, Rosa Aldora; Boru Situmorang, Novidawati; Marbun, Romauli Anna Teresia (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2020)
Introduction: Basil leaf (Ocimum basilicum L.) is one of the most accessible natural plant in Asia such as Indonesia. Basil leaf vegetation contains a lot of flavonoid compounds and essential oils that have the effect as antibacterial because it can inhibit the growth of bacteria Streptococcus mutans cause dental caries. Streptococcus mutans is a round gram-positive bacteria that typically form pairs or chains during its growth. The purpose of this research is to know the antibacterial effectivity of ethanol extract of basil leaves (Ocimum basilicum L.) on the growth of Streptococcus mutans bacteria.This research was conducted with laboratory experimental research method. Basil lean ethanol extract was prepared by using maseration extraction method. Method: The method used in the inhibitory test using diffusion of the disc with 5 samples in each treatment group. The sample consisted of 5 treatment groups, ethanol extract of basil leaves with concentration of 100%, 80%, 60%, 40% and 20%. Result: The result of this study showed that ethanol extract of basil leaves with 100% concentration had inhibitory power of 10,26 mm (strong category), 80% of 9,65 mm (medium category), 60% by 8,12 mm (medium category), 40% by 7,33 mm (medium category), and 20% by 6,90 mm (medium category). Conclusion: The conclusion of this research proves that basil leaf ethanol extract has antibacterial power agains Streptococcus mutans bacteria with effective concentration is 100% with strong category equal to 10,26 mm.